High-current ion linac calculation - Gavrilov, N.M.; Bogatchenkov, D.A.; Komarov, D.A.; Struckov, J.N.; Krasnogolovets, M.A.; Volkolupov, Yu.Ya. (Вопросы атомной науки и техники, 2001)
The research on multibeam ion accelerators has been carried. Full analysis of the oscillating system on example of a HCIL cell containing a pair of conducting rings (CR) with drift tubes (DT) and a central drift channel was carried out. High-current electronic beam is used as an electromagnetic power supply, which not exclude an external power source. Interaction factor of an electronic beam with a field of about 100%, kiloampere currents and megawatt power levels allows to produce a compact electron-beam pumping system with drift tubes shorter then wavelength.